Potensi Pemanfaatan Biogas Dari Sampah Organik Sebagai Sumber Energi Terbarukan - Aulia Wulansari Agustin; Sudarti, Sudarti; Yushardi, Yushardi (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Waste is one of the most serious problems experienced by the world, and Indonesia is no exception. Waste generated by human activity or nature will continue to increase, if this waste is not managed properly, it will cause new problems such as being a source of disease, can cause global warming and can cause foul odors. On the other hand, energy demand will continue to increase along with the increasing population and economic growth. The limitations of available energy sources are dwindling, thus demanding attention to switch energy sources using renewable energy sources to meet the increasing energy needs. This study aims to identify the potential utilization of biogas from organic waste in various potential applications that can support renewable energy sources. In this research, the method used is a literature study which is analyzed by descriptive analysis method. The results obtained in this study are the making of biogas is done by several processes and using a digester. This biogas has the potential to be a renewable energy source because it contains very high methane and carbon dioxide compounds. Biogas from organic materials can be used as cooking fuel, a substitute for petrol (gasoline), lighting, and power generation. Of course, the utilization of biogas from organic waste can reduce the amount of waste supply and become a source of energy that is very beneficial for daily life.